Continuous Positive Airway Pressure and Breathlessness in Obese Patients with Obstructive Sleep Apnea: A Pilot Study - Xiao, Sichang (Sleep, 2016)
STUDY OBJECTIVES: Continuous positive airway pressure (CPAP) is an effective treatment for obstructive sleep apnea (OSA). However, long-term compliance with CPAP is limited. We tested the hypothesis that CPAP levels routinely used during sleep increase neural respiratory drive (NRD) and breathlessness, which may discourage compliance. METHODS: This was an observational physiological cohort study in a respiratory physiology and sleep unit, University Hospital. Patients with a body mass index (BMI) > 25 kg/m(2) and confirmed OSA were studied supine and awake on CPAP (4–20 cm H2O, increments of 2 cm H2O/3 min). We measured NRD during awake CPAP titration in obese subjects to quantify the response to the load of the respiratory system and compared it to the CPAP used for nocturnal treatment, with the modified Borg Scale (mBorg) for dyspnea recorded (from 0 to 10 points, with higher numbers indicating more breathlessness). RESULTS: Fifteen patients (age 48 ± 10 years, 12 male, BMI 38.9 ± 5.8 kg/m(2)) with OSA (AHI 32.2 ± 21.1/h, 95(th) percentile of CPAP 14.1 ± 3.8 cm H2O) were studied and NRD (electromyogram of the parasternal intercostals, EMGpara; EMG of the external oblique, EMGabdomen) was recorded (awake, supine). Awake, EMGpara declined from baseline to 70.2% ± 17.1% when CPAP of 10.7 ± 3.4 cm H2O (P = 0.026) was applied. Further increase in CPAP led to a rise in EMGpara and increased breathlessness (P = 0.02). CPAP compliance (nights used) correlated negatively with mBorg scores (r = −0.738, P = 0.006). CONCLUSIONS: Awake, the respiratory system is maximally offloaded with lower than therapeutic CPAP levels in obese patients with OSA. Levels of NRD observed at effective CPAP levels while asleep are associated with breathlessness which may limit long-term CPAP compliance. CITATION: Xiao S, Bastianpillai J, Ratneswaran C, Pengo MF, Luo Y, Jolley CJ, Moxham J, Steier J. Continuous positive airway pressure and breathlessness in obese patients with obstructive sleep apnea: a pilot study. SLEEP 2016;39(6):1201–1210.